OsJAZ1 Attenuates Drought Resistance by Regulating JA and ABA Signaling in Rice - Fu, Jie; Wu, Hua; Ma, Siqi; Xiang, Denghao; Liu, Ruyi; Xiong, Lizhong (Frontiers in Plant Science, 2017)
Jasmonates (JA) and abscisic acid (ABA) are phytohormones known play important roles in plant response and adaptation to various abiotic stresses including salinity, drought, wounding, and cold. JAZ (JASMONATE ZIM-domain) proteins have been reported to play negative roles in JA signaling. However, direct evidence is still lacking that JAZ proteins regulate drought resistance. In this study, OsJAZ1 was investigated for its role in drought resistance in rice. Expression of OsJAZ1 was strongly responsive to JA treatment, and it was slightly responsive to ABA, salicylic acid, and abiotic stresses including drought, salinity, and cold. The OsJAZ1-overexpression rice plants were more sensitive to drought stress treatment than the wild-type rice Zhonghua 11 (ZH11) at both the seedling and reproductive stages, while the jaz1 T-DNA insertion mutant plants showed increased drought tolerance compared to the wild-type plants. The OsJAZ1-overexpression plants were hyposensitive to MeJA and ABA, whereas the jaz1 mutant plants were hypersensitive to MeJA and ABA. In addition, there were significant differences in shoot and root length between the OsJAZ1 transgenic and wild-type plants under the MeJA and ABA treatments. A subcellular localization assay indicated that OsJAZ1 was localized in both the nucleus and cytoplasm. Transcriptome profiling analysis by RNA-seq revealed that the expression levels of many genes in the ABA and JA signaling pathways exhibited significant differences between the OsJAZ1-overexpression plants and wild-type ZH11 under drought stress treatment. Quantitative real-time PCR confirmed the expression profiles of some of the differentially expressed genes, including OsNCED4, OsLEA3, RAB21, OsbHLH006, OsbHLH148, OsDREB1A, OsDREB1B, SNAC1, and OsCCD1. These results together suggest that OsJAZ1 plays a role in regulating the drought resistance of rice partially via the ABA and JA pathways.